(untitled) (Estudios humanísticos. Geografía, historia y arte, 1996)
The article departs to the fact of the celebration of the first general elections in Spain with a direct system. The objetive are to analise the way how to comed to the approbation of this direct system, as soon his development and the social and politics repercussions of the direct system implantation in the León province.